2020
DOI: 10.1016/j.cmi.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The recent emergence of a highly related virulent Clostridium difficile clade with unique characteristics

Abstract: Objectives: Clostridium difficile is a major global human pathogen divided into five clades, of which clade 3 is the least characterized and consists predominantly of PCR ribotype (RT) 023 strains. Our aim was to analyse and characterize this clade. Methods: In this cohort study the clinical presentation of C. difficile RT023 infections was analysed in comparison with known 'hypervirulent' and non-hypervirulent strains, using data from the Netherlands national C. difficile surveillance programme. European RT02… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…Minor clone strains of C. difficile are well-known to often remain susceptible to fluoroquinolones (Wiuff et al, 2011;Knight et al, 2015;Seugendo et al, 2018) or evolve various mutations in the gyrB gene and display reduced resistance to this group of antibiotics (Lee et al, 2014;Wasels et al, 2015;Shaw et al, 2019;Vernon et al, 2019). Though some of the genetic alterations in gyrB will confer some fitness gain onto the isolates (Wasels et al, 2015;Vernon et al, 2019), it is also well-established that these mutations will accord just a low-level resistance to moxifloxacin rendering the isolates "vulnerable" to exposure (Wasels et al, 2015;Vernon et al, 2019).…”
Section: Difficilementioning
confidence: 99%
“…Minor clone strains of C. difficile are well-known to often remain susceptible to fluoroquinolones (Wiuff et al, 2011;Knight et al, 2015;Seugendo et al, 2018) or evolve various mutations in the gyrB gene and display reduced resistance to this group of antibiotics (Lee et al, 2014;Wasels et al, 2015;Shaw et al, 2019;Vernon et al, 2019). Though some of the genetic alterations in gyrB will confer some fitness gain onto the isolates (Wasels et al, 2015;Vernon et al, 2019), it is also well-established that these mutations will accord just a low-level resistance to moxifloxacin rendering the isolates "vulnerable" to exposure (Wasels et al, 2015;Vernon et al, 2019).…”
Section: Difficilementioning
confidence: 99%
“…Several highly virulent CDT-producing strains, including ST1 (PCR ribotype [RT] 027), a lineage associated with major hospital outbreaks in North America, Europe, and Latin America ( He et al, 2013 ), are found in clade 2 (C2). Comparatively little is known about clade 3 (C3), although it contains ST5 (RT 023), a toxigenic CDT-producing strain with characteristics that may make laboratory detection difficult ( Shaw et al, 2020 ). C. difficile ST37 (RT 017) is found in clade 4 (C4) and, despite the absence of a toxin A gene, is responsible for much of the endemic CDI burden in Asia ( Imwattana et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that the different RTs within a certain toxinotype may have evolved from a common ancestral strain. This event could be due to independent mutations or horizontal gene transfer (HGT) that occurred in the PaLoc of an ancestral strain [4]. In a previous study, a sequence analysis of the 16S rRNA gene revealed that the strains with toxinotypes V, VI, and XI had a single base change when compared to the VPI 10463 strain [30].…”
Section: Discussionmentioning
confidence: 99%